Association between apolipoprotein E gene polymorphism and depression. Issue 8 (August 2015) - Feng, Fang; Lu, Shan-Shan; Hu, Cai-Yun; Gong, Feng-Feng; Qian, Zhen-Zhong; Yang, Hui-Yun; Wu, Yi-Le; Zhao, Yuan-Yuan; Bi, Peng; Sun, Ye-Huan
Abstract: We performed an updated meta-analysis to obtain a more precise estimation of the relationship between apolipoprotein E (ApoE) gene polymorphism and susceptibility to depression, as previous reports have been inconsistent. Twenty studies with 2286 depression patients and 3845 controls were included. Odds ratios (OR) with 95% confidence intervals (CI) were calculated to assess the association between ApoE gene polymorphism and depression using a random effects model. Results showed a significant association between ApoE gene polymorphism and susceptibility to depression in the overall population (ε2/ε3 genotype versus ε3/ε3: OR 0.76, 95% CI 0.59–0.99). Subgroup analyses indicated an association in the Caucasian population (ε2 allele versus ε3: OR 0.75, 95% CI 0.58–0.97) as well as in late-life depression (LLD) patients (ε3/ε4 genotype versus ε3/ε3: OR 1.34, 95% CI 1.07–1.68, and ε4 allele versus ε3: OR 1.30, 95% CI 1.06–1.59). We concluded that the ε2/ε3 genotype likely provided a protective effect against depression in the overall population and the ε2 allele acted as a protective factor for depression in the Caucasian population while the ε4 allele and ε3/ε4 genotype were associated with an increased risk of depression in the LLD subjects.